Autoimmune hemolytic anemia- an initial presentation in childhood systemic lupus erythematosus - S. Giriyan, Sujata; Priya, Priya; P., Reddy (Tropical Journal of Pathology and Microbiology, 2019)
Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease that can involve any organ system. It predominantly affects women aged 20 to 40 years. In 10% to 15% of patients, the diagnosis is first established during childhood. Childhood SLE is greater in severity, abrupt with atypical presentation at onset. A 12-year-old girl presented with fever of 8 days and vomiting of 2 days duration. On examination there was pallor and hepatospleenomegaly. Hematologic investigations showed picture of hemolytic anemia. RBCs showed auto-agglutination. Suspecting autoimmune hemolytic anemia, Direct Coombs test was done and was positive. Patient later developed malar rash and hematuria. Suspecting the cause of autoimmune hemolytic anemia to be SLE, Antinuclear antibody, Anti double stranded DNA antibody, Anti Smith antibody were done and showed positive result. Hence the diagnosis was confirmed to be Autoimmune Hemolytic Anemia Due to Systemic Lupus Erythematosus.